Plasma based Synthesis and Modification of Nanomaterials - Pohl, Pawel (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book, entitled "Plasma-Based Synthesis and Modification of Nanomaterials" is a collection of nine original research articles devoted to the application of different atmospheric pressure (APPs) and low-pressure (LPPs) plasmas for the synthesis or modification of various nanomaterials (NMs) of exceptional properties. These articles also show the structural and morphological characterization of the synthesized NMs and their further interesting and unique applications in different areas of science and technology. The readers interested in the capabilities of plasma-based treatments will quickly be convinced that APPs and LPPs enable one to efficiently synthesize or modify differentiated NMs using a minimal number of operations. Indeed, the presented procedures are eco-friendly and usually involve single-step processes, thus considerably lowering labor investment and costs. As a result, the production of new NMs and their functionalization is more straightforward and can be carried out on a much larger scale compared to other methods and procedures involving complex chemical treatments and processes. The size and morphology, as well as the structural and optical properties of the resulting NMs are tunable and tailorable. In addition to the desirable and reproducible physical dimensions, crystallinity, functionality, and spectral properties of the resultant NMs, the NMs fabricated and/or modified with the aid of APPs are commonly ready-to-use prior to their specific applications, without any initial pre-treatments.